Risk assessment of trace metal-polluted coastal sediments on Hainan Island: A full-scale set of 474 geographical locations covering the entire island. Issue 1 (15th December 2017) - Li, Feng; Lin, Ze-Feng; Wen, Jia-Sheng; Wei, Yan-Sha; Gan, Hua-Yang; He, Hai-Jun; Lin, Jin-Qin; Xia, Zhen; Chen, Bi-Shuang; Guo, Wen-Jie; Tan, Cha-Sheng; Cai, Hua-Yang
Abstract: Hainan Island is the second largest island and one of the most famous tourist destinations in China, but sediment contamination by trace metals in coastal areas is a major issue. However, full-scale risk assessments of trace metal-polluted coastal sediments are lacking. In this study, coastal surface sediments from 474 geographical locations covering almost the entire island were collected to identify risk-related variables. Controlling factors and possible sources of trace metals were identified, and the toxicity effects were carefully evaluated. Our results suggest that trace-metal pollution in coastal sediments, which was mainly caused by Pb, Zn and Cu emissions, has primarily resulted from industrial sewage and shipping activities and has threatened the offshore ecosystem of Hainan Island and warrants extensive consideration. This is the first study that has systematically investigated trace metal-polluted coastal sediments throughout the entirety of Hainan Island and provides solid evidence for sustainable marine management in the region. Highlights: AVS and SEM concentrations, including controlling factors in coastal surface sediments, were first obtained throughout Hainan Island. The SEM/AVS ratio indicated that adverse biological effects may be expected in 121 stations on Hainan Island. The SEM-AVS differences indicated adverse biological effects may be expected in 1 station in the North-eastern area. ([SEM]–[AVS])/ f OC indicated adverse biological effects may be expected in 7 stations on Hainan Island. Possible trace metal sources were comprehensively discussed.